Principal Professionalism in Improving the Quality of Education in Senior High School - Susanti, Ani; Riyanto, Yatim; Sigit, Bambang (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research aims to analyze and describe the professionalism of school principals in improving the quality of education based on the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 40 of 2021. The research method is a qualitative case study approach. Data collection techniques with interviews, observation, and documentation. Data processing techniques with reduction, data presentation, and concluding. Data validity technique with source and technique triangulation. Based on the research conducted, the following research results were obtained: aspects of learning development, the principal of Hang Tuah 1 Senior High School Surabaya conducts an annual performance evaluation and competency improvement program for teachers and education staff. In terms of school culture, the principal of Hang Tuah 1 Senior High School Surabaya develops a vision and mission, creates a safe, disciplined school environment, works according to duties, and collaborates. In terms of improving the quality of learning processes and outcomes, the principal of Hang Tuah 1 Senior High School Surabaya conducts coaching, training, supervision, file examination, and evaluation of school programs. In terms of entrepreneurship development, the principal of Hang Tuah 1 Senior High School Surabaya opened a hotel school. In terms of assessing the performance of teachers and education staff, the principal of Hang Tuah 1 Senior High School Surabaya formed a performance appraisal team. In the aspect of teacher guidance and coaching, the principal of Hang Tuah 1 Senior High School Surabaya provided mentoring and teacher competency training.